Indonesian English Teachers’ Work Engagement and Attitudes towards the Use of Instructional Technology: A Survey Study - Adaninggar Septi Subekti; Lemmuela Alvita Kurniawati (Universitas Hamzanwadi, 2022)
The present study was conducted to investigate the level of work engagement of Indonesian high school teachers of English and its relationship with their attitudes towards the use of instructional technology (IT) during the Covid-19-driven online instruction. The study employed a survey method of distributing a Google Form questionnaire and a total of 114 teachers participated in the study. It was found that the participants generally reported a high level of work engagement in their English Language teaching (ELT) profession. Though at least 93% of the participants reported their engagement in the profession in all questionnaire items, they seemed to be less sure about their level of engagement in terms of striving for excellence in the profession seen from lower